Ketidakmerataan Pembangunan Di Nagori Simbolon Tengkoh Dan Huta Saribu Raya Satu Di Kecamatan Panombeian Panei Kabupaten Simalungun - Nisyadella Ramadhani; Monika Siallagan; Demak Angelita Purba; Grace Rismaulina Naibaho; Jindri Nuansa Nasution; Stepan Hojora Purba; Daffa Rifanda Lubis; Rizky Sahertian; Dian G. Purba Tambak (Jurnal Multidisiplin Indonesia, 2023)
The aim of this research is to determine the development of infrastructure and technology in Saribu Raya Satu hamlet. The research method used is a qualitative research method. Qualitative methods are research methods that are descriptive and tend to use analysis. Research results: Village development is the government's focus in creating prosperity for rural communities. Even though the infrastructure program in Nagori Simbolon Tengkoh and Huta Saribu Raya Satu has had a positive impact, there are still challenges such as unequal access, especially in remote hamlets such as Saribu Raya Satu. Internet network problems and inadequate school facilities in this hamlet are obstacles to improving the quality of education. The government's role is very important in overcoming these obstacles so that village development can run evenly and have a wider positive impact. Village development also requires support for facilities and infrastructure, especially in the education and health sectors. The main challenge lies in the limited access of rural communities to development policy making, which then results in obstacles in coordination and relations between the government and villages. Efforts to improve communication and active participation of village communities are the keys to overcoming these obstacles so that village development can run more effectively and evenly.